Análise sobre a atuação de profissionais da psicologia com adolescentes em cumprimento de medidas socioeducativas em unidades de internação - Gomes, Ariane Rico (Universidade Federal de São Carlos, 2021)
Since the creation of SINASE, psychologists have been designated as part of the minimum team in the care of adolescents in compliance of socio-educational measures. Thus, an increase was expected, both in the number of professionals working in this segment and in the scientific productions in the area, which underlie the performance. Based on these considerations, this research was divided into two studies. In Study 1, a Systematic Literature Review (SLR) was carried out in order to analyze Brazilian scientific production in the field of psychology, with respect to the theme of socio-education, since the creation of SINASE (2006) to the year 2020. Twenty-six studies were found, the majority being cross-sectional exploratory, mostly developed in the Southeast and South regions, and focusing on adolescents in inpatient units. The lack of studies on scientifically validated interventions and longitudinal studies was highlighted. In addition, the need for investment in psychological science in other regions of the country was evidenced, considering that the criminal trajectories can vary according to the context in which the adolescent is inserted. In Study 2, we sought to characterize the profile of psychology professionals working in internment units in the state of São Paulo, as well as to verify the knowledge of these professionals about the guidelines that support their practices, and their perception of their own performance. For this purpose, a self-administered questionnaire was built, administered via Google Forms, consisting of 4 sections, namely: 1) sociodemographic data (such as gender, age, income, length of experience), 2) higher education (type of university time of training, postgraduation), 3) Theoretical and practical knowledge of the guidelines to professional practice (SINASE, 2006; 2012 and CFP, 2010) and 4) perception of their own professional performance. The questionnaire underwent content validation, with 51 items referring to the last two sections. The instrument was answered by 93 psychology professionals working in internment units in the state of São Paulo. Most of the sample consisted by women, with an average age of 43.3 years, graduated in private universities and hired through public examination. Participants obtained high scores, both in knowledge about the guidelines for action and in their perception of the work performed. The need for studies in different regions of the country is discussed, as well as the importance of the topic of socio-education in psychology training.
Analysis about performance of psychology professionals with adolescents in cumpliance with socio-educational measures in internation units
Keywords: Psicologia; Adolescentes; Socioeducação; Internação; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::DESENVOLVIMENTO SOCIAL E DA PERSONALIDADE